Neuronavigation-guided anterior interhemispheric transcallosal approach for tumors of the ventricles. - Wong Achi, Xavier; Chong, César (Revista Argentina de Neurocirugía, 2021)
Introduction: The vast majority of lesions originating within the ventricular system are benign and rare. Surgical excision is the treatment of choice and a challenge for the neurosurgeon given its depth and relation to surrounding neurovascular structures. Objective: To discuss the election of the appropriate surgical approach for intraventricular tumors and to demonstrate the utility of the transcallosal approach in the resection of lesions located in the third ventricle. Methods: The authors describe the surgical technique used, results and complications, based on a concise review of the literature. The clinical and surgical history of a 40-year-old patient with a lesion that occupies the Monro foramen was used retrospectively as an illustration. Results: Total excision was achieved, the patient was discharged asymptomatic, with subsequent MRI follow-up. Conclusions: The described approach constitutes a versatile technique, facilitating total excision and reducing the risk of postoperative complications. From our perspective, the transcallosal approach seems less traumatic and more direct regardless of the surgeon’s skills and habit. The video can be found here: https://youtu.be/0NPCGW2H3GA